Erythrocyte membrane permeability for a series of diols - Gordiyenko, O.I.; Linnik, T.P.; Gordiyenko, E.O. (Elsevier B.V., 2004)
Erythrocyte membrane permeability coefficients for a series of diols have been defined by the method developed. The method is based on the physical and mathematical modeling of hypotonic hemolysis process. There have been also determined membrane permeability coefficients for erythrocytes treated with p-chloromercuribenzenesulfonic acid monosodium salt (pCMBS), which is known to block aqueous protein channels. Permeating process is shown to be conditioned both by hydrophilic/hydrophobic properties of the molecules and their geometrical parameters. The obtained results propose that, when exceeding the molecules diameter over a value of 4 A ̊, the permeability coefficient reduces due to decreasing of flow through the aqueous protein pores of a constant size. Permeability coefficients for comparatively hydrophobic molecules are almost directly proportional to the coefficients of partition between hydrophobic and hydrophilic phases, by pointing to a lipid way of permeation of these molecules through erythrocyte membranes.
Keywords: Erythrocyte membrane; Permeability; Diols